Extrapancreatic Nerve Plexus Invasion on Imaging Predicts Poor Survival After Upfront Surgery for Anatomically Resectable Pancreatic Cancer. Issue 5 (May 2020) - Sugimoto, Motokazu; Kobayashi, Tatsushi; Kobayashi, Shin; Takahashi, Shinichiro; Konishi, Masaru; Mitsunaga, Shuichi; Ikeda, Masafumi; Gotohda, Naoto
Abstract : Objectives: This study aimed to analyze the risk factors for poor survival of the patients with anatomically resectable pancreatic ductal adenocarcinoma (PDAC), focusing on detailed computed tomography (CT) findings of tumor extent to the peripancreatic tissue. Methods: The study included 192 patients who underwent upfront pancreaticoduodenectomy for anatomically resectable PDAC. Preoperative CT images were rereviewed by an experienced radiologist for the pattern of tumor extension to the surrounding tissue: biliary, duodenal, serosal, retroperitoneal, portal venous, arterial, extrapancreatic nerve plexus, and other-organ invasion. Imaging findings and other clinical data that could be obtained before surgery were evaluated for their association with a shorter disease-specific survival (DSS) and recurrence-free survival (RFS). Results: Of the 192 anatomically resectable PDAC patients, extrapancreatic nerve plexus invasion was observed on CT in 38 patients (20%), and this finding was independently associated with a shorter DSS (hazard ratio, 2.258; P < 0.001) and RFS (hazard ratio, 2.665; P < 0.001). The median survival of patients with and without extrapancreatic nerve plexus invasion on CT was 19.7 versus 38.5 months ( P < 0.001). Conclusions: Extrapancreatic nerve plexus invasion was shown as an only CT finding associated with a shorter DSS and RFS after upfront surgery for the patients with anatomically resectable PDAC.